Dynamical neural activation in human brain during face recognition. (19th October 2011) - Gandhi, T.; Swami, P.; Santhosh, J.; Anand, S.
This paper presents an experimental model and a set of stipulations for understanding neural progression in human brain while distinguishing familiar faces, and relationship between recognition and other aspects of face processing. Dynamical imagery stimuli of familiar and unfamiliar faces were shown to healthy individuals and were asked to recognise them as quickly and accurately as possible. Results obtained from the non-parametric analysis of the recorded multivariate data indicate that process of structural decoding of unfamiliar faces occurring inside the brain is delayed in comparison with familiar face probably due to few distinctive information that we derive from seen faces appear to influence the processing performance of the brain during the task.